Sumber Ajaran Islam - Agus Rifki Ridwan; Syarwan Hd; Septi Wahyu Ningsih; Saribun Saribun (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Islamic teachings are a life guide for muslims that originate from various important references. These sources of Islamic teachings are the basis for living a life in accordance with Allah's commands and the guidance of His Messenger. There are four main sources recognized in Islamic teachings, namely the Al-Qur'an, Hadith, Ijma', and Qiyas. The Al-Qur'an is the holy book of Muslims which is believed to be a revelation from Allah SWT which was conveyed to the Prophet Muhammad SAW, while the Hadith is a collection of sayings, actions and approvals of the Prophet Muhammad SAW which serve as a guide in understanding and practicing Islamic teachings. This article aims to examine the role and importance of these four sources in shaping the law, ethics and social life of Muslims. Through qualitative research methods with a descriptive-analytical approach, the research results show that the Al-Qur'an and Hadith are closely related in shaping Muslims' understanding of religion. In addition, this article also examines how ulama use these two sources in establishing Islamic law (shariah) and how these teachings are applied in different socio-cultural contexts. Thus, this research strengthens the importance of understanding in depth the two sources of Islamic teachings in order to apply them in everyday life.